Comparative Analysis of Indonesia and China on the Copyright Protection Law for Computer Software - Wiwin Widianingsih (Justice Voice, 2025)
This study examines the copyright regulations on computer software in Indonesia and China, focusing on their alignment with international standards such as the TRIPs Agreement, Berne Convention, and WIPO Copyright Treaty. Using a normative legal research method with a comparative law approach, the analysis identifies key similarities and differences in definitions, rights granted, duration of protection, enforcement mechanisms, and sanctions. Findings show that China has advantages in providing specific regulations, clearer definitions, longer protection periods, and proactive enforcement mechanisms, while Indonesia stands out in the application of performance rights and stronger criminal sanctions. However, both countries still face significant challenges: Indonesia’s absence of specific regulations and reliance on a complaint-based enforcement system, and China’s relatively weak criminal penalties. The study concludes that adopting best practices from each jurisdiction could significantly enhance the effectiveness of copyright protection for computer software, especially in addressing high rates of software piracy. This analysis contributes to the discourse on intellectual property law reform in the digital era by providing policy recommendations for stronger, more comprehensive legal frameworks.